Analysis of Learning Difficulties of Grade IV Elementary School Students on Fractal Materials Reviewed from Numeracy Ability and Self-Efficacy - Aprillia Putri Pradinar; Wiryanto; Endah Budi Rahaju (Papanda Publisher, 2026)
Difficulty understanding the concept of fractions is still a major challenge for elementary school students and has an impact on numeracy skills and self-efficacy in learning mathematics. This study aims to analyze the learning difficulties of grade IV students of SD Muhammadiyah 1 Taman on fractional material reviewed from numeracy ability and self-efficacy. The research method used a quantitative descriptive approach involving 25 students of grade IV A. Data were collected through numeracy ability tests, Bandura scale-based self-efficacy questionnaires, and structured interviews. The results showed that students' numeracy ability was in the medium category with an average achievement of 56.8%, with dominant difficulties in the aspects of fraction comparison (42%) and mixed fraction counting operations (38%). Student self-efficacy was also moderately (62.7%), with the magnitude dimension obtaining the lowest score (56%). The Pearson correlation test showed a strong positive relationship between numeracy ability and self-efficacy (r = 0.724; p < 0.01), while regression analysis showed a 52.4% contribution to numeracy ability to self-efficacy. The results of the interviews confirmed that students better understand the concept of fractions through concrete media and contextual learning. This study recommends the application of ethnomathematics-based fractional learning model with a strategy of increasing self-efficacy through positive reinforcement and scaffolding.